Effects of detergent micelles on lipid binding to proteins in electrospray ionization mass spectrometry - Landreh, M; Costeira-Paulo, J; Gault, J; Marklund, E; Robinson, C (American Chemical Society, 2017)
A wide variety of biological processes rely upon interactions between proteins and lipids, ranging from molecular transport to the organization of the cell membrane. It was recently established that electrospray ionization mass spectrometry (ESI-MS) is capable of capturing transient interactions between membrane proteins and their lipid environment, and a detailed understanding of the underlying processes is therefore of high importance. Here, we apply ESI-MS to investigate the factors that govern complex formation in solution and gas phases by comparing nonselective lipid binding with soluble and membrane proteins. We find that exogenously added lipids did not bind to soluble proteins, suggesting that lipids have a low propensity to form electrospray ionization adducts. The presence of detergents at increasing micelle concentrations, on the other hand, resulted in moderate lipid binding to soluble proteins. A direct ESI-MS comparison of lipid binding to the soluble protein serum albumin and to the integral membrane protein NapA shows that soluble proteins acquire fewer lipid adducts. Our results suggest that protein-lipid complexes form via contacts between proteins and mixed lipid/detergent micelles. For soluble proteins, these complexes arise from nonspecific contacts between the protein and detergent/lipid micelles in the electrospray droplet. For membrane proteins, lipids are incorporated into the surrounding micelle in solution, and complex formation occurs independently of the ESI process. We conclude that the lipids in the resulting complexes interact predominantly with sites located in the transmembrane segments, resulting in nativelike complexes that can be interrogated by MS.